Analisis Evaluasi Tiang untuk Stabilisasi Lereng dengan Metode Elemen Hingga Dua Dimensi - Karina Meilawati Eka Putri; Griselda Junianda Velantika; Rizqi Alghiffary; Elok Dewi Widowati; Muhamad Fauzan Akbari (Universitas Muhammadiyah Surabaya, 2026)
Landslides due to slope instability are natural phenomena that can lead to substantial damage to infrastructure, loss of property, and human fatalities. Slope-stabilizing piles are among the most effective and widely used recently to increase slope stability. This paper presents an evaluation of slope-stabilizing piles using 2D finite element method (FEM), including a parametric study on the effects of pile diameter, pile spacing, and pile length on the pile responses, such as bending moment and deformation. The analysis conducted in this research employed the 2D FEM. FEM modeling was performed with the plane strain model and the Hardening Soil (HS) soil constitutive model. A parametric study was conducted by varying the pile parameters, such as pile length (12, 16, and 20 meters), diameter of pile (0.6, 0.8, 1.0, and 1.2 meters), and pile spacing (1.5D, 2D, 3D, and 4D). Based on the analysis results, pile length shows the most significant influence on slope stability; an increase in pile length is proportional to an increase of the factor of safety and bending moments but inversely proportional to the resulting deformation. On the other hand, pile diameter was found to have no significant impact on the improvement of the Factor of Safety in this study, although dimensional variations affect internal forces, specifically regarding deformation and bending moment distribution within the pile. Furthermore, increasing the spacing between piles tends to decrease the factor of safety because it weakens the soil arching mechanism, which subsequently increases deformation at the pile head. This research suggested that the optimization of slope stability is more dependent on the embedment length of pile and pile spacing rather than the pile diameter.